2021
DOI: 10.1186/s13287-021-02244-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human umbilical cord mesenchymal stem cells attenuate the inflammation of severe steroid-resistant asthma by reshaping macrophage polarization

Abstract: Background Severe, steroid-resistant asthma (SSRA) is a serious clinical problem in asthma management. Affected patients have severe clinical symptoms, worsened quality of life, and do not respond to steroid, a mainstay steroid treatment of asthma. Thus, effective therapies are urgently needed. Exosomes derived from mesenchymal stem cell (MSC-Exo) has become attractive candidates for the lung inflammatory diseases through its immunomodulatory effects. In this study, we explored the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…The therapeutic role of MSC-EVs in asthma has been investigated both in vitro and in vivo. Dong et al (Dong et al, 2021) found that human UC-MSCs derived EVs inhibited inflammation by reshaping macrophage polarization via blocking tumor necrosis factor receptor associated factor 1 (TRAF1). Fang et al (Fang et al, 2020a) also investigated effects of MSC-EVs on macrophages in asthma disease model, and their research suggested that EVs from human iPSC-MSCs inhibited the recruitment and polarization of lung macrophages in mice with allergic airway inflammation.…”
Section: Asthmamentioning
confidence: 99%
“…The therapeutic role of MSC-EVs in asthma has been investigated both in vitro and in vivo. Dong et al (Dong et al, 2021) found that human UC-MSCs derived EVs inhibited inflammation by reshaping macrophage polarization via blocking tumor necrosis factor receptor associated factor 1 (TRAF1). Fang et al (Fang et al, 2020a) also investigated effects of MSC-EVs on macrophages in asthma disease model, and their research suggested that EVs from human iPSC-MSCs inhibited the recruitment and polarization of lung macrophages in mice with allergic airway inflammation.…”
Section: Asthmamentioning
confidence: 99%
“…In the steroid-resistant mouse model, Bing Dong and his colleagues found that intratracheal administration of exosomes treatment reduced inflammation and reduced M1 macrophages, and promoted M2 macrophages. This effect could achieve by inhibiting the TNF receptor-associated factor 1 (TRAF1) ( Dong et al, 2021 ). In this way, MSCs promote the polarization of macrophages from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype and regulate through related proteins, exosomes, and inflammatory factors.…”
Section: Modulation Of Different Immune Cells By Mesenchymal Stem Cellsmentioning
confidence: 99%
“…HucMSCs were placed in osteogenic medium (0.1 mM dexamethasone, 10 mM β-glycerophosphate and 50 mM ascorbyl phosphate) or adipogenic medium (Cyagen Biosciences, CA, USA). Two weeks later, the osteogenic and adipogenic differentiation potentials were evaluated by Alizarin Red and Oil Red O staining [16,17].…”
Section: Collection and Identi Cation Of Hucmscsmentioning
confidence: 99%